2020
DOI: 10.7160/aol.2020.1200108
|View full text |Cite
|
Sign up to set email alerts
|

CRM and its Importance for Business Competitiveness

Abstract: This paper deals with the Customer Relationship Management (CRM) system with emphasis on the importance for the competitiveness of a business. The aim of the present article is to seek whether a business pursues customer value on a regular basis regardless of its size. Monitoring customer value can thus be one of the criteria that measure the success of implementing an overall customer relationship management concept in a particular business. CRM system is also used in agribusiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In recent years, a number of studies have been devoted to enterprise transformations and business environment changes due to sustainable development implementations. Most of these studies have focused on specific sustainable development issues such as changes in business ethics preferences and corporate social responsibility advancements (Elhennawy, 2019; Metzker et al, 2021; Pelikánová et al, 2021; Wang et al, 2020), business management systems improvements, including customer relationship management (Matsenko et al, 2021; Stuchlý et al, 2020), networking systems management (Do Rosário & De Jesus Breda, 2021), development of new business activities (Bilan et al, 2020) among others. This study systematically reviews three strands of research that have identified various contemporary challenges covered within enterprise development, sustainable development, and the business environment.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of studies have been devoted to enterprise transformations and business environment changes due to sustainable development implementations. Most of these studies have focused on specific sustainable development issues such as changes in business ethics preferences and corporate social responsibility advancements (Elhennawy, 2019; Metzker et al, 2021; Pelikánová et al, 2021; Wang et al, 2020), business management systems improvements, including customer relationship management (Matsenko et al, 2021; Stuchlý et al, 2020), networking systems management (Do Rosário & De Jesus Breda, 2021), development of new business activities (Bilan et al, 2020) among others. This study systematically reviews three strands of research that have identified various contemporary challenges covered within enterprise development, sustainable development, and the business environment.…”
Section: Introductionmentioning
confidence: 99%